2014
DOI: 10.1002/cplu.201402176
|View full text |Cite
|
Sign up to set email alerts
|

Activated‐Carbon‐Supported Gold–Cesium(I) as Highly Effective Catalysts for Hydrochlorination of Acetylene to Vinyl Chloride

Abstract: The synthesis of vinyl chloride from acetylene by hydrochlorination has gained tremendous interest in coal‐based chemistry. Bimetallic gold–cesium(I)/activated carbon (AuCsI/AC) catalysts were found to have a higher catalytic activity and stability for acetylene hydrochlorination when compared with gold catalysts. Over 1 Au4 CsI/AC catalysts, the maximum conversion of acetylene was 94 % and there was only 5 % C2H2 conversion loss after 50 h of running time. Moreover, the 1 Au4 CsI/AC catalyst delivered a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 29 publications
(25 reference statements)
3
44
0
Order By: Relevance
“…[25,26] Thus, before the aluminosilicate gel is obtained, QHS activation must be achieved by alkaline fusion. [27] In the fused QHS, one zeolitic phase and NaAlSiO 4 formed, but the quartz phase remained. The removal of quartz impurities relies on a modified liquid-transport, gravity-based, spatial separation technique, which was first introduced by the Holmes group.…”
Section: Synthesis Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…[25,26] Thus, before the aluminosilicate gel is obtained, QHS activation must be achieved by alkaline fusion. [27] In the fused QHS, one zeolitic phase and NaAlSiO 4 formed, but the quartz phase remained. The removal of quartz impurities relies on a modified liquid-transport, gravity-based, spatial separation technique, which was first introduced by the Holmes group.…”
Section: Synthesis Strategymentioning
confidence: 97%
“…They have been used in fiber optic telecommunication systems, night-vision equipment, anticancer drugs, and metal-ion catalysts. [1][2][3][4] Brine is an important cesium resource. China, especially Qinghai, is very rich in salt lake brine resources.…”
Section: Introductionmentioning
confidence: 99%
“…In his initial study the activity of metal catalysts is found to be related with the associated metal ions' standard electrode potentials [1] and AuCl 3 has a higher electrode potential. Subsequently, there was a great deal of research on gold catalysts [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, Au-based catalysts do not have their advantages of economic performance because of the high price of Au.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the desorption temperature of Mo 3 Ti 1 N/AC was the lowest at around 440 • C and adsorption was thus weak relative to that of other catalysts. Although TiN/AC had a low quantity of adsorbed acetylene, its desorption temperature was the highest, which suggested that the binding between the ingredient and acetylene was strong [35]. In this reaction, a higher degree of activation usually corresponds to stronger binding and a greater quantity of adsorbed HCl.…”
Section: Characteristics Of Fresh and Used Samplesmentioning
confidence: 99%